Effect of interference on the press fitting of railway wheel and axle assemblies - Theingi Nwe; Monsak Pimsarn (My University, 2021)
Abstract Press fitting is one of the common fastening methods used to assemble mechanical components. It has also received considerable critical many industrial applications, for example, railway wheel and axle are usually assembled by press-fitting. This process generates high stress on the axle-fillet area and fatigue is generally initiated due to the stress concentration. This paper attempts to propose the stress distribution and deformation of a railway axle. Various interference clearances were analyzed using finite element method. The contact pressure at the axle wheel seat along the axial direction was examined as it significantly influences the press-fitted components life. The analytical results from Lame’s theory [1] were compared with finite element analysis results for the wheel and axle press-fitting process. The results obtained from both methods were in good agreement and the maximum relative error of the contact pressure is by 11.08 %. Additionally, the results show that the Von-Mises stresses on the axle wheel seat and fillet areas were found to be increased if the interference increased.
Keywords: Fillet (mechanics); Interference fit; Mechanical stress and fatigue analysis